Plataforma educativa para guardas ecológicos inanapoxu bora (2021)
The Amazon comprises the largest forest area in the world and is one of the largest regions of the country, due to its extreme jungle condition there is an important parallel, it has an uncountable environmental, cultural and social wealth; but at the same time it faces great challenges such as connectivity with the center of the country, the protection of environmental resources and cultural wealth. The place of intervention is delimited as “Amazonian trapezoid” since it is there where most of the population of the region is concentrated and the two most important populated centers are located (Leticia and Puerto Nariño). The proposal as a master plan is based on research based on the exploration and studies of the region (flora, fauna and culture), locating main study centers in Puerto Nariño from where a route to the other nuclei located within the jungle bordering the Amacayacu natural national park and is complemented by a proposal for river connectivity at the regional level through the Loretoyacú River and the Amazon to face connectivity problems.